Integration of Tarbawi Tafsir Values in the Early Childhood Education Curriculum - Junaedi Abdullah; Iskandar Mirza (Penerbit Hellow Pustaka, 2025)
The integration of Tarbawi Tafsir values in the Early Childhood Education (PAUD) curriculum aims to shape children's character and morals from an early age through moral and spiritual values taken from the interpretation of the Koran. Values such as honesty, patience, responsibility, and compassion can be taught using stories, play activities, and social interactions relevant to early childhood development through intra-curricular activities, play activities and community and parent-based activities.